Study on Floral Biology of Gladiolus Genotypes - Poon, Tul Bahadur; Rao, T. M.; Kumar, D. P.; Venugopalan, R.; Dhananjaya, M. V. (Nepal Journal of Science and Technology, 2010)
This study was conducted in the field of Indian Institute of Horticultural Research (IIHR), Bangalore, India. The experiment was laid out in a randomized complete block design with different genotypes replicated three times. Observations were recorded for sixteen floral characters. Among different genotypes, viz., ‘Arka Kesar', ‘H.S.84-7-11' and ‘Shobha' were early in respect of days to spike emergence, full spike emergence, the first bud showing color, basal bud loosening and flowering. Duration of spike emergence to flowering was long in ‘Psittacinus hybrid' (14.18 days),' H.S.87-22-11'(13.17 days) and ‘Dhiraj' (13.13 days). Duration of first floret bud loosening to complete opening of florets was short in ‘Shobha' (21 hours 31 minutes), ‘H.S.84-7-11'(21 hours 53 minutes) and ‘Darshan ‘(21 hours 58 minutes). Duration of initiation and completion of anther dehiscence was long in ‘Psittacinus hybrid ‘ (5 hours 19 minutes) and ‘H.S. 82-11-27' (5 hours 7 minutes). Duration of initiation to completion of stigma receptivity was long in ‘H.S. 87-22-1' (4 days 1 hour 37 minutes), ‘Tilak' (4 days 1 hour) and ‘H.S.87-1-1'(3 days 22 hours 59 minutes). Key words: Anther dehiscence; Gladiolus; Spike; Stigma receptivity DOI: 10.3126/njst.v10i0.2821 Nepal Journal of Science and Technology Volume 10, 2009 December Page: 37-43